A Cost‐Effective Workfare System Succeeding in Attracting Applicants to Labor Markets. Issue 3 (September 2015) - Nakamura, Yui
<x xml:space="preserve">Abstract</x> Poverty alleviation programs are inefficient when the existence of asymmetric information hinders the government from understanding the capabilities of its program participants. Workfare is known as one solution to this problem. This study classifies workfare systems into two types: (1) those that provide unskilled jobs and (2) those that provide a variety of jobs, including both unskilled and skilled jobs. Next, it shows that the latter succeeds in terms of cost‐effectiveness and in attracting participants to the private sector labor market after completion of the program. Moreover, this study indicates that such a policy can increase social welfare when compared with the former type of poverty alleviation program.